Postcolonial ecocriticism and the comparison of southeast Asian and Caribbean literatures / Christopher Lloyd De Shield - Christopher , Lloyd De Shield (2016)

(untitled)
This thesis consists of two parts. In part one, I argue that diverse works – hailing from the otherwise disparate archipelagic regions of the Caribbean and Southeast Asia – can be placed into productive relation. To perform this work, I use a methodological lens developed and derived from two very different sources of inspiration. First, I draw upon seminal and contemporary work in the burgeoning discipline of ―postcolonial ecocriticism.‖ The second source of inspiration is classical work in comparative anatomy and developmental vertebrate biology, more specifically, the model of differentiation presented by the concept of ―analogous structures.‖ I spend considerable space in part one of this thesis developing and attuning this specific comparative methodology to Caribbean and Southeast Asian particularities. In Chapter Three, I place the two regions under the rubric of ―analogous structures‖ and demonstrate how the two regions began to be thought of together historically, through the colonial imaginary, and on to the postcolonial imaginary. I build on this historical and literary scholarship in an effort to justify and ground subsequent comparisons. Part one concludes with a survey of the ―comparative gesture‖ in recent works of postcolonial ecocriticism and a claim, namely: as a theoretical method, postcolonial ecocriticism can recuperate the work of analogy in literary comparison. In part two, three chapters of analysis are presented as case studies for the specific comparative approach developed and advocated in this thesis. In Chapter Four, I consider Ishak Haji Muhammad‘s Putera Gunung Tahan (1937) alongside Alejo Carpentier‘s El Reino de Este Mundo (1943) so that each might comment on the other‘s magical representation of a specific colonial epistemological struggle. In Chapter Five I juxtapose Lloyd Fernando‘s Scorpion Orchid (1976), Wilson Harris‘s Palace of the Peacock (1960), and Zee Edgell‘s Beka Lamb (1982) to complicate the critical reduction of the authors‘ fictional narratives to the logic of national social prescription. iv This chapter reveals how the textual figure of the female is problematically used in the narratives to resolve issues of socio-racial national integration through analogical recourse to nature and land. Finally, in Chapter Six, I look at two famous works of Caribbean and Southeast Asian provenance respectively, Jean Rhys‘s Wide Sargasso Sea (1966) and José Rizal‘s Noli Me Tangere (1887) to show how the differences in status held by both work and author in their respective regions is belied by the comparatively similar literary configurations they each display. My conclusion synthesises the findings in a qualified defence of the work of analogy in postcolonial literary comparison against claims of ahistoricisation. I conclude with the claim that ecocritical perspectives in postcolonial literary analysis sustain the politically-useful work of mimetic reading while providing a suitably universal theoretical category that yet protects the works against over-contextualisation and reductivist forms of allegorical reading.